2022
DOI: 10.1037/cou0000614
|View full text |Cite
|
Sign up to set email alerts
|

The effects of group counseling and self-affirmation on stigma and group relationship development: A replication and extension.

Abstract: The stigma of seeking counseling and negative attitudes about counseling are primary barriers to its use. In the only known study examining the utility of attending a group counseling session to ameliorate stigma (no control group), participation was associated with reductions in self-stigma (Wade et al., 2011). Self-affirmation interventions have shown promising results in reducing stigma and promoting positive expectations about counseling, but no research has examined its effects on a counseling session. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…Stigma related to HIV infection remains a concern in Sub-Saharan Africa (SSA) and influences depression among HIV-positive mothers (22). A study elsewhere indicated that health education during counselling reduces self-stigma among patients (23). Another study after a Quasi-experimental study indicated that Psychoeducation reduced self-stigma among patients with schizophrenia with an effect of (F(1,19)=5.52; p<0.05) (24).…”
Section: Discussionmentioning
confidence: 99%
“…Stigma related to HIV infection remains a concern in Sub-Saharan Africa (SSA) and influences depression among HIV-positive mothers (22). A study elsewhere indicated that health education during counselling reduces self-stigma among patients (23). Another study after a Quasi-experimental study indicated that Psychoeducation reduced self-stigma among patients with schizophrenia with an effect of (F(1,19)=5.52; p<0.05) (24).…”
Section: Discussionmentioning
confidence: 99%
“…Second, Owen et al (2013) found that higher self-stigma was associated with lower ratings of the alliance in a sample of 91 college students receiving individual psychotherapy. Most recently, Seidman et al (2022) found a negative but not significant relationship among a sample of 138 college students attending a one-time group therapy session. However, a limitation of these studies is that the results reflect cross-sectional data.…”
Section: Overview Of the Present Studymentioning
confidence: 99%
“…Furthermore, empathy promotes emotional growth and the development of adaptive coping skills in clients, which helps their longterm well-being. Finally, empathy is a transforming force that enables clients to begin a journey of self-discovery, resilience, and psychological healing within a counseling setting [10][11][12][13].…”
Section: Building Resilience and Coping Skillsmentioning
confidence: 99%